The Impact of the No-Plastic-Bag Campaign on Customer Repurchase Intentions and its mechanism in the Modern Trade Business in Bangkok - Ratasuk, Akaraphun (Asia Social Issues, 2021)
This research investigated the impact of the no-plastic-bag campaign on customer repurchase intentions in the modern trade business in Bangkok. Six hundred customers of modern trade stores in Bangkok were initially approached using a stratified random sampling method, but only 418 of them participated in this survey. The partial least squares structural equation results indicated that the no-plastic-bag campaign promotes customer repurchase intentions (β=0.098; p=0.038). Also, the no-plastic-bag campaign could indirectly foster customer repurchase intentions via both enhancing brand image (t=7.379; p<0.001) and increasing customers’ perceived value (t=2.806; p<0.001). Therefore, it can be concluded that the no-plastic-bag campaign benefits modern trade businesses, promoting customer repurchase intentions by enhancing their brand image and customer perceived values. This research also explored the mediating roles of brand image and perceived value on the relationship. These findings provide new knowledge of the no plastic bag campaign’s contribution to customer repurchase intentions which has not yet been investigated, and the mechanism linking them together. The results can be applied as a guideline to other modern-trade businesses or other businesses to enhance their brand image and promote customer repurchase intentions, which is crucial to sustainable business accomplishment. This research investigated the impact of the no-plastic-bag campaign on customer repurchase intentions in the modern trade business in Bangkok. Six hundred customers of modern trade stores in Bangkok were initially approached using a stratified random sampling method, but only 418 of them participated in this survey. The partial least squares structural equation results indicated that the no-plastic-bag campaign promotes customer repurchase intentions (β=0.098; p=0.038). Also, the no-plastic-bag campaign could indirectly foster customer repurchase intentions via both enhancing brand image (t=7.379; p<0.001) and increasing customers’ perceived value (t=2.806; p<0.001). Therefore, it can be concluded that the no-plastic-bag campaign benefits modern trade businesses, promoting customer repurchase intentions by enhancing their brand image and customer perceived values. This research also explored the mediating roles of brand image and perceived value on the relationship. These findings provide new knowledge of the no plastic bag campaign’s contribution to customer repurchase intentions which has not yet been investigated, and the mechanism linking them together. The results can be applied as a guideline to other modern-trade businesses or other businesses to enhance their brand image and promote customer repurchase intentions, which is crucial to sustainable business accomplishment.